The Complicated Effects of Extracellular Vesicles and Their Cargos on Embryo Implantation - Jiang, Nan-Xing; Li, Xue-Lian (Frontiers in Endocrinology, 2021)
As a rate-limiting step in pregnancy, embryo implantation is highly dependent on intercellular communication. Extracellular vesicles (EVs) are newly identified to be important in the course of intercellular communication. EVs have been isolated from a wide variety of biofluids and tissues, including plasma, liver, uterine, semen, embryo, etc. The present and future use of EVs not only as biomarkers, but also as targeting drug delivery system, is promisingly pave the way for advanced comprehension of implantation failure in reproductive diseases. However, as the precise mechanisms of EVs in embryo implantation has not been elucidated yet. Herein, we summarize the current knowledge on the diverse effects of EVs from various sources and their cargos such as microRNA, long non-coding RNA, protein, etc. on embryo implantation, and the potential mechanisms of EVs in reproductive diseases such as recurrent implantation failure, polycystic ovary syndrome and endometriosis. It is essential to note that many of the biologically plausible functions of EVs in embryo implantation discussed in present literatures still need further research in vivo.